Gingipain proteases from the bacterium Porphyromonas gingivalis confer protection against airway viral infection - Carlos J. Rodriguez Hernandez; Alonso Cruz-Cruz; Chandra L. Shrestha; Marina Terekhova; Phylip Chen; John Perpich; Barbara Potempa; Katherine Carey; Michelle Rohlfing; Mark E. Peeples; Mitchell H. Grayson; Jan Potempa; et al. (Proceedings of the National Academy of Sciences, 2026)
Physical interactions with bacterial colonizers at mucosal barrier surfaces can have beneficial or detrimental effects on viral infectivity and transmission. The oropharyngeal mucosal surface is a major portal of entry for many pathogenic respiratory viruses, such as respiratory syncytial virus (RSV), and also harbors a rich and diverse microbiome. Whether oropharyngeal bacteria directly or indirectly influence host susceptibility to respiratory viruses remains unknown. Here, we show that Porphyromonas gingivalis , an oral pathobiont, potently and uniquely suppresses airway epithelial antiviral immunity by degrading interferons (IFNs) and transcriptionally repressing multiple IFN-stimulated genes (ISGs), which are essential for providing resistance to viral infection. Despite inducing a state of IFN hyporesponsiveness, we found that P. gingivalis counterintuitively protected against severe infection by RSV and the closely related murine-specific Sendai virus (SeV) in two independent models: human airway bronchial epithelial transwell cultures and airway infection in mice. This protection was conferred by the activity of P. gingivalis cysteine proteases (gingipains) that cleaved envelope glycoproteins on RSV and SeV, thereby impairing their infectious capacity. Thus, our data show a nuanced role for P. gingivalis in modulating host susceptibility to viral infection. While P. gingivalis can significantly inhibit host IFN responses, its proteases preemptively reduce viral infectious capacity, protecting the host from severe damage associated with respiratory infections.